High-photoresponsivity heterojunction based on MoTe2/2D electron gas at the LaAlO3/SrTiO3 interface. (18th May 2023) - Zhou, Xiaowei; Li, Bocheng; Tian, Xiaochen; Jiang, Yucheng; Zhao, Run; Zhao, Meng; Gao, Ju; Xing, Jie; Qiu, Jie; Liu, Guozhen
Abstract: Two-dimensional (2D) transition metal dichalcogenides (TMDs) are ideal elements for many optoelectronic devices owing to their outstanding optoelectrical performance under visible and infrared light. Heterostructures composed of TMDs and other non-TMD materials may exhibit rich properties. In this study, a high-performance heterojunction based on 2D MoTe2 and 2D electron gas (2DEG) at the LaAlO3 /SrTiO3 interface was fabricated. The device exhibits good current rectification properties with a high rectification ratio exceeding 10 3 and a low leakage current (∼1 nA at −6 V bias). Moreover, a high photoresponsivity of ∼800 A W −1 and a large specific detectivity of 4 × 10 12 Jones at 405 nm were also obtained at room temperature. Heterostructures based on 2D TMDs and oxide 2DEG are expected to become essential elements in multifunctional microdevices and optoelectronic devices.